Cereblon (CRBN) gene polymorphisms predict clinical response and progression-free survival in relapsed/refractory multiple myeloma patients treated with lenalidomide: a pharmacogenetic study from the IMMEnSE consortium. Issue 3 (23rd February 2020) - Iskierka-Jażdżewska, Elżbieta; Canzian, Federico; Stępień, Anna; Martino, Alessandro; Campa, Daniele; Stein, Angelica; Krawczyk-Kuliś, Małgorzata; Rybicka-Ramos, Malwina; Kyrcz-Krzemień, Sławomira; Butrym, Aleksandra; Mazur, Grzegorz; Jurczyszyn, Artur; et al.
Abstract: Cereblon (CRBN) is crucial for antiproliferative and immunomodulatory properties of immunomodulatory drugs. The objective of this study was to verify whether germline single nucleotide polymorphisms (SNPs) in the CRBN gene may influence response to lenalidomide in multiple myeloma (MM). Fourteen tagging SNPs covering the genetic variability in the CRBN gene region were genotyped in 167 Polish patients with refractory/relapsed MM treated with lenalidomide-based regimens. We found that carriers of minor alleles of two studied CRBN SNPs rs1714327G > C (OR = 0.26; 95% CI = 0.1–0.67; p  = .0055, Bonferroni corrected p  = .033) and rs1705814T > C (OR = 0.22; 95% CI = 0.07–0.65; p  = .0063, Bonferroni corrected p  = .037) were significantly associated with lower probability of achievement at least partial remission while treated with lenalidomide-based regimens, using the dominant inheritance model. Moreover, one of these SNPs, namely rs1705814T > C, was correlated with shorter progression-free survival (HR = 2.49; 95%CI = 1.31–4.74, p  = .0054, Bonferroni corrected p  = .033). It is suggested that selected germline CRBN allelic variants (rs1714327G > C and rs1705814T > C) affect lenalidomide efficacy in patients with relapsed/refractory MM.